Interpersonal communication analysis of students at Schools that use social media in the New Normal Era - Yuniar, Riean Rachma; Juliawati, Dosi; Jamin, Ahmad; Yandri, Hengki (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2020)
Interpersonal communication is one of the main asset of a person to succeed in daily life including in the school. Good interpersonal communication skills will support students' success in the school, but not all students have interpersonal communication skills, especially those who are active in social media. Thus, the aim of this research is to reveal the interpersonal communication of students who use social media. This research used a descriptive quantitative method with the number of respondents were 31 students of seventh grade at State Junior High School of 24 Kerinci which was taken by using the purposive sampling technique. Data were revealed by using the scale of inter-private communication and then, the data collected were analyzed by using the percentage formula.Â  Afterwards, the interpretation of the acquisition score of research results done by using the ideal score. The results reveal that in general, the students who use social media in the school haveÂ  poor interpersonal communication